Molecular taxonomy of Osedax (Annelida: Siboglinidae) in the Southern Ocean. (14th May 2014) - Amon, Diva J.; Wiklund, Helena; Dahlgren, Thomas G.; Copley, Jonathan T.; Smith, Craig R.; Jamieson, Alan J.; Glover, Adrian G.
<x xml:space="preserve">Abstract</x> We report the discovery of three new species of Osedax in the deep Southern Ocean, expanding the diversity and geographical range of this genus of bone‐eating worms. Osedax rogersi sp. n. and Osedax crouchi sp. n. were found on a whale skeleton at 1444 m in the Kemp Caldera in the East Scotia Sea during the Chemosynthetic Ecosystems of the Southern Ocean (ChEsSo) project. The recently described species, Osedax antarcticus, found on whale bones implanted at a depth of 550–650 m off Smith Island in the Bransfield Strait, was also found inhabiting the whale skeleton in the Kemp Caldera. Osedax crouchi as well as another new species Osedax nordenskjoeldi sp. n. have also been found on the implanted whale bones off Smith Island. These two localities are approximately 1800 km apart demonstrating a wide distribution of species within the genus. We describe the three new species, O. rogersi, O. crouchi and O. nordenskjoeldi and report the second record of O. antarcticus. We also present a new phylogenetic analysis for Osedax, including data examining genetic connectivity between the Scotia Arc and the Bransfield Strait.